Prinsip kerjasama dalam wawancara di acara televisi “Quotidien” - Armry Zai, Saga; Ismail, Subur; Andika, Yunilis (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2023)
This study aims to find out the types of cooperative principle maxims according to Grice's theory which were used in an interview on the 8th of September 2021 edition of the television show